2002
DOI: 10.1097/00002030-200212060-00006
|View full text |Cite
|
Sign up to set email alerts
|

HIV and antiretroviral drug distribution in plasma and fat tissue of HIV-infected patients with lipodystrophy

Abstract: Our results suggest that HIV does not replicate and does not integrate its genome in fat tissue in patients with fat redistribution abnormalities. In patients with effective nadir plasma concentrations of PI and NNRTI, determination of concentration in adipocyte lysates suggests that PI may diffuse in fat tissue with the same pattern of distribution for all structurally related components tested. NNRTI present a high affinity for fat tissue and may accumulate in this compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 10 publications
1
36
0
1
Order By: Relevance
“…NNRTIs represent a promising approach to combine antiviral efficiency and limited adverse effects. However, recent papers have reported that efavirenz could accumulate in adipose tissue (24) and inhibit triacylglycerol accumulation in mouse preadipose clonal lines (25). We show in this paper that, despite a high extracellular concentration of nevirapine, the intracellular accumulation of this NNRTI was low compared with PIs.…”
Section: Effect Of Pis On Human Adipocytesmentioning
confidence: 47%
“…NNRTIs represent a promising approach to combine antiviral efficiency and limited adverse effects. However, recent papers have reported that efavirenz could accumulate in adipose tissue (24) and inhibit triacylglycerol accumulation in mouse preadipose clonal lines (25). We show in this paper that, despite a high extracellular concentration of nevirapine, the intracellular accumulation of this NNRTI was low compared with PIs.…”
Section: Effect Of Pis On Human Adipocytesmentioning
confidence: 47%
“…Moreover, it should be noted that rilpivirine in cell culture studies is added to serumfree adipocyte culture medium; thus, dose for dose, the effective concentration of rilpivirine in cell culture may be higher than the actual free rilpivirine concentration in blood, where serum proteins may bind substantial amounts of drug (15). In contrast with other NNRTIs, including efavirenz, where information on differential tissue distribution in patients is available (8), there is no data relating to the potential accumulation of rilpivirine at higher concentrations in adipose tissue than in blood.…”
Section: Discussionmentioning
confidence: 99%
“…68 However, the results of further studies led to a questioning of this possibility. 69,70 More recently, it has been reported that human adipocytes in primary culture are susceptible to HIV-1 infection, and exposure to high levels of TNFa, as occurs in adipose tissue of HALS patients, leads to effective HIV-1 replication and production by adipocytes. 71 On the other hand, cellular components other than adipocytes that are present inside adipose tissue depots may also be the targets of HIV-1 infection.…”
Section: Lipomatosis In Hals Reveals a Potential For Brown Adipocyte mentioning
confidence: 99%